Performative cross-gendering and disciplinary border crossing - Čale Feldman, Lada (Array, 2000)
The interest for the third gender collides with the theoretical approach to gender as a performative construction, often blurring not only the borders between the two sex-gender poles, but also between disciplines called upon to theorize the sexual criss-crossings. The paper questions one of such border-crossings, the one between theatre and theory, since performance and performative derive principally from the already hybrid field of Schechners performance theory.